Does integration lead to lower costs of equity?. (February 2017) - Dye, Jessica; Gilbert, Aaron; Pacheco, Gail
Recent evidence has suggested that the benefits of equity market integration may not be shared equally by all firms. Making use of a firm-level measure of integration we investigate whether one of the documented benefits of equity market integration, lower cost of equity capital (COEC), holds for all Australian firms. Empirical evidence suggests that the degree of integration is reflected in firm COEC, albeit not in the expected way. Our results indicate that increased integration at the firm level leaves firms exposed to higher COEC when world market conditions are volatile.